Employee Financial Wellness Programs: Promising New Benefit for Frontline Workers?. (19th August 2020) - Despard, Mathieu R.; Frank-Miller, Ellen; Zeng, Yingying; Fox-Dichter, Sophia; Germain, Geraldine; Grinstein-Weiss, Michal; Covington, Meredith
Interest among employers is growing in employee financial wellness programs (EFWPs), a new type of benefit to address financial stress among employees. EFWP benefits include financial counseling, small-dollar loans, and savings programs that address employees' nonretirement financial needs. Little evidence exists concerning the availability and use of and outcomes associated with EFWPs, especially among low- and moderate-income (LMI) workers who may be in the greatest need of these benefits. We present findings concerning awareness and use of EFWPs from a national survey of LMI workers ( N = 16, 650). Availability of different EFWP benefits ranged from 11 to 15% and over a third of workers were unaware of whether their employer offered an EFWP. Experiencing financial difficulties predicted both EFWP awareness and use suggesting that employers should take time to assess employees' specific financial challenges to select benefits. Yet, use of EFWPs by LMI workers may suggest the need for better compensation and work conditions.